A potential regulatory loop between Lin28B:miR-212 in androgen-independent prostate cancer - BORREGO-DIAZ, EMMA; POWERS, BENJAMIN C; AZIZOV, VUGAR; LOVELL, SCOTT; REYES, RUBEN; CHAPMAN, BRADLEY; TAWFIK, OSSAMA; McGREGOR, DOUGLAS; DIAZ, FRANCISCO J; WANG, XINKUN; VAN VELDHUIZEN, PETER (International journal of oncology, 2014)
Lin28 is a family of RNA binding proteins and microRNA regulators. Two members of this family have been identified: Lin28A and Lin28B, which are encoded by genes localized in different chromosomes but share a high degree of sequence identity. The role of Lin28B in androgen-independent prostate cancer (AIPC) is not well understood. Lin28B is expressed in all grades of prostatic carcinomas and prostate cancer cell lines, but not in normal prostate tissue. In this study we found that Lin28B co-localized in the nucleus and cytoplasm of the DU145 AIPC. The expression of Lin28B protein positively correlated with the expression of the c-Myc protein in the prostate cancer cell lines and silencing of Lin28B also correlated with a lower expression of the c-Myc protein, but not with the downregulation of c-Myc messenger RNA (mRNA) in the DU145 AIPC cells. We hypothesized that Lin28B regulates the expression of c-Myc protein by altering intermediate c-Myc suppressors. Therefore, a microRNA profile of DU145 cells was performed after Lin28B siRNA silencing. Nineteen microRNAs were upregulated and eleven microRNAs were downregulated. The most upregulated microRNAs were miR-212 and miR-2278. Prior reports have found that miR-212 is suppressed in prostate cancer. We then ran TargetScan software to find potential target mRNAs of miR-212 and miR-2278, and it predicted Lin28B mRNA as a potential target of miR-212, but not miR-2278. TargetScan also predicted that c-Myc mRNA is not a potential target of miR-212 or miR-2278. These observations suggest that Lin28B:miR-212 may work as a regulatory loop in androgen-independent prostate cancer. Furthermore, we report a predictive 2-fold symmetric model generated by the superposition of the Lin28A structure onto the I-TASSER model of Lin28B. This structural model of Lin28B suggests that it shows unique microRNA binding characteristics. Thus, if Lin28B were to bind miRNAs in a manner similar to Lin28A, conformational changes would be necessary to prevent steric clashes in the C-terminal and linker regions between the CSD and ZNF domains.